Compound Attitude Maneuver and Collision Avoiding Control for a Novel Noncontact Close-Proximity Formation Satellite Architecture - He Liao; Jinjin Xie; Xiaodong Zhou; Chuang Yao; Zhongxing Tang; Yanbin Zhao; Jirong Qi (International Journal of Aerospace Engineering)
In order to achieve the attitude maneuver performance of the noncontact close-proximity formation satellite architecture, this paper presents a compound control strategy with variable-parameter sliding mode control and disturbance observer-based feedforward compensation. Firstly, the variable-parameter sliding mode control is proposed to guarantee the attitude maneuver performance of the payload module. Secondly, the collision avoiding control with disturbance observer-based feedforward compensation is proposed to guarantee the synchronization of the two separated modules within the small air clearance constraint of the noncontact Lorentz actuator. Finally, a physical air-floating platform is established to verify the effectiveness of the proposed approach.